Evaluation Study On Teacher Competency Physical Education, Sports And Health (PJOK) In Pesawaran District - Rahmat Hermawan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
Based on observations so far, physical education and sports teachers in Lampung in the implementation of their learning have not been effective(Hermawan, 2020), is no exception, of course, in Pesawaran Regency. This study aims to obtain a general description of the competence of physical education and sports teachers in Pesawaran Regency, including pedagogic, professional, personality, and social competencies.Method research used is survey method with qualitative descriptive approach. The population of this research isall PJOK teachers (SD, SMP and SMA/SMK) in Pesawaran Regency, as many as 136 people. Data collection techniques using instrumentsobservations, interviews, documentation and questionnaires. Data analysis usingqualitative descriptive analysis approach through triangulation, and the results of the study can be concluded namely (1) The profile of PJOK teachers in Pesawaran is generally still relatively productive, which is in the range of 31-35 years, namely 37 people (27.21%) and in the age range 41-45 years, namely 36 people (26.47%)especially for elementary school teachers, (2) the pedagogical competence of teachers is in accordance with the provisions of the legislation, namely being able to (a) understand students, (b) make learning designs, (c) carry out conducive learning, and (d) design and carry out evaluations of learning outcomes on an ongoing basis, (3) In terms of personality competencies, teachers have behaviors that can be imitated by students, (4). In terms of social competence, the teachers are able to communicate and interact effectively with various parties, and (5) In terms of professional competition, most of the teachers have obtained certification, namely 94 people (65.12%).